2022
DOI: 10.3390/horticulturae8100887
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of Plectranthus amboinicus (Lour.) Spreng. with Different Yeast Strains: Morphological Performance, Productivity, Phenotypic Plasticity, and Antioxidant Activity

Abstract: Due to the growing knowledge about the microorganism–plant relationship, medicinal plants have gained great attention in their bio fertilization programs using biostimulants based on microorganisms. Plectranthus amboinicus (Lour.) Spreng. is a perennial herb belonging to the family Lamiaceae and has therapeutic and nutritional properties attributed to its natural phytochemical compounds, which are highly valued in the pharmaceutical industry. A pot experiment was conducted to evaluate the efficiency of Rhodoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Total protein was assessed using the semi-micro Kjeldahl technique [ 39 ]. Total carbohydrates were measured colorimetrically as previously described by Alshallash et al [ 40 ] using the phenol–sulfuric acid technique [ 41 ]. For extracting total phenolics and DPPH in the seeds, 1 g of seed samples was mixed with 10 mL of ethanol (60%) and left for 3 h under shaking conditions at room temperature; then, the mixture was centrifuged at 3000× g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein was assessed using the semi-micro Kjeldahl technique [ 39 ]. Total carbohydrates were measured colorimetrically as previously described by Alshallash et al [ 40 ] using the phenol–sulfuric acid technique [ 41 ]. For extracting total phenolics and DPPH in the seeds, 1 g of seed samples was mixed with 10 mL of ethanol (60%) and left for 3 h under shaking conditions at room temperature; then, the mixture was centrifuged at 3000× g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…All N-fixing bacteria strains used in this study showed significant enhancements in roselle growth and yield under saline conditions. These improvements may be due to the phytohormones produced by N-fixers, including IAA [42], which enhances division, elongation, and differentiation of plant cells [43,44]; tryptophol; and indole butyric acid (IBA), which stimulate plant growth indirectly [45,46]. NFB can increase plant growth by elevating the fixation of atmospheric nitrogen, mineral solubilization, and siderophore production.…”
Section: Discussionmentioning
confidence: 99%
“…A study with Plectranthus amboinicus showed a lower plasticity index for the leaf number (0.23 and 0.28) and oil percent (0.24 and 0.25). The branch number, essential oil yield, and herb and RDW traits showed great enhancements that were affected by yeast applications, and they gave the highest results [68].…”
Section: Discussionmentioning
confidence: 99%